High-power, single-mode fiber lasers advance - Schreiber, Thomas; Tünnermann, Andreas; Thoss, Andreas (Laser Focus World, 2017)
Funded by the German government and in collaboration with TRUMPF (Ditzingen, Germany), Active Fiber Systems, Jenoptik, and the Leibniz Institute of Photonic Technology, a team of scientists from Friedrich Schiller University and the Fraunhofer Institute for Applied Optics and Precision Engineering (Jena, Germany) analyzed the challenges for upscaling such lasers and then developed new fibers to overcome the limitations. The team successfully completed a series of tests showing 4.3 kW single-mode output, in which the fiber laser output was limited only by the input pump power. The challenges for such a single-mode high-power fiber laser can be grouped into three fields, improved pumping, designing an active fiber with low optical losses working in single-mode operation only, and measuring the resulting radiation correctly. Within the design of an active fiber for high-power single-mode operation, there are two general sets of parameters to optimize, doping and geometry. All parameters have to be determined for minimal losses, single-mode operation, and, finally, high-power amplification. Measuring all aspects of a high-power fiber laser is a major effort and requires specific equipment for several different tasks. For a full characterization of the fiber, dopant concentration, refractive index profiles, and fiber core attenuation were determined. During the fiber amplifier test mentioned above, the TMI threshold was determined using a small fraction of the power analyzed with a photodiode. The onset of power fluctuations is rather sudden and substantial.
CRIS-Team Scopus Importer:2023-04-20